Sexual Dimorphism in Horizontal Length and Gonial Angle of the Mandible: A Radiographic Study - Afshar, Azar; Fadaei Fathabadi, Fatemeh (Novelty in Biomedicine, 2023)
Background: Forensic anthropology is one of the most important sub-fields of physical anthropology in which anthropometric indicators are used to examine the biological characteristics of corpses. In the meantime, the mandible bone is regarded as a significant bone following the pelvic bone due to its high resistance and dimorphism characteristics. Thus, this study aims to investigate the two parameters of the body’s horizontal length and the mandible’s gonial angle using radiographic images. Materials and Methods: In this study, 120 orthopantomography images were used to examine the parameters of the horizontal length of the body and the gonial angle. The parameters were quantitatively checked using EASY-DENT software. Then, the statistical data were analyzed using Prism software version 9.0 and T-test. Results: In this study, the mean horizontal length of the mandible body in women and men was 97.16 and 83.97 mm, respectively, and the data analysis showed a significant difference between the two sexes. Also, the gonial angle in men was measured as 173.1 and 166.9 degrees on average on the right and left sides, respectively, and on average as 144.6 and 142.1 degrees on the right and left sides in women. The data analysis indicated a significant difference between the two sexes, while the gonial angle was greater in men than women. Conclusion: According to the findings of this study, the two parameters of the horizontal length of the body and the gonial angle of the mandible can be significant indicators in forensic anthropology and other related studies.